PREVALENCE OF AVIAN INFLUENZA VIRUS (AIV) (SUBTYPE A/H5N1) IN COMMERCIAL POULTRY FARMS IN JOS SOUTH LOCAL GOVERNMENT AREA OF PLATEAU STATE, NIGERIA FOR SUSTAINABLE DEVELOPMENT (FUDMA JOURNAL OF SCIENCES, 2023)
An investigation to determine the prevalence rate of Avian Influenza virus (AIV) sub type A/H5N1 among birds in five selected commercial poultry farms located in Jos south Local Government Area of Plateau State was conducted. A total of 200 swab samples (comprising of 40 from each site) collected from the trachea and cochlea of the birds were analyzed using standardIsolation/serology methods for the isolation and identification of the virus. Out of the 200 samples analyzed, 68 were found to be positive with Avian Influenza virus subtype A/H5N1 representing 34% overall prevalence rate.  Samples analyzed from Rantya had the highest prevalence rate as 34 out of the 40 had Avian Influenza virus (AIV) sub type A/H5N1 representing 85% prevalent rate. This was closely followed by samples from Federal Low coast with 19 cases representing 47 %. Samples from Ray field had the lowest cases of the viruses as only 3 out of the 40 had the Influenza virus representing 7.5%. A failed biosafety measure has been identified as a major contributing factor in the spread of Avian Influenza virus among poultry birds. To this end, the adoption of biosafety measures among others could curtail the spread of the virus among poultry farms.
Keywords: Avian Influenza Virus, Poultry Farms, Prevalence, Biosecurity